2021
DOI: 10.1186/s12870-021-02996-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of iron bioavailability is independent from iron concentration in a diverse winter wheat mapping population

Abstract: Background Anemia is thought to affect up to 1.6 billion people worldwide. One of the major contributors to low iron (Fe) absorption is a higher proportion of cereals compared to meats and pulse crops in people’s diets. This has now become a problem in both the developed and developing world, as a result of both modern food choice and food availability. Bread wheat accounts for 20 % of the calories consumed by humans and is an important source of protein, vitamins and minerals meaning it could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Additional small genetic effects may explain the remaining heritability but were not detected using the statistical power available in this study. Wright et al ( 2021 ) investigated similar traits in the same population with a similar number of lines and found that the probability of detecting small effect QTL (explaining <10% of the variation) was very low, unless the trait heritability was very high. We acknowledge that low heritability of some traits and testing in only two trial years may limit the extent to which results can be interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Additional small genetic effects may explain the remaining heritability but were not detected using the statistical power available in this study. Wright et al ( 2021 ) investigated similar traits in the same population with a similar number of lines and found that the probability of detecting small effect QTL (explaining <10% of the variation) was very low, unless the trait heritability was very high. We acknowledge that low heritability of some traits and testing in only two trial years may limit the extent to which results can be interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…While future research is required to determine whether elevated levels of phenolics that stimulate and inhibit Fe uptake in the human gut can help alleviate the anaemia seen in Ethiopian children [ 67 ], the significance of the SNP in the tef F3’H gene Et_s3159-0.29-1.mrna1, which explains a large proportion of the variation in kaempferol glycoside and quercetin glycoside levels, suggest this might be a breeding target to improve Fe bioavailability in tef, as kaempferol glycoside is known to promote Fe absorption while quercetin glycoside inhibits Fe absorption in cell assays [ 60 ]. In addition, phenolic compounds have also been found to influence other agronomic traits, including tolerance to both biotic and abiotic stress [ 16 , 60 , 61 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in our understanding of the genetics of tef include a fairly complete genome assembly, the release of gene models, as well as a number of RNASeq datasets which are all publicly available [ 11 ] . These allow for translation of knowledge on grain fortification from other species, supporting more rapid advancements in efforts to improve the nutritional potential of tef [ 12 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, increasing Fe content in wheat seeds seems to not correlate with higher Fe bioavailability and the underlying genetic regions controlling Fe content not found, yet, to colocalize with increased Fe absorption. In addition, phytate content also does not correlate with Fe bioavailability, leading to the conclusion that phytate binding may be insufficient to explain the lack of correlation between Fe bioavailability and Fe content ( Wright et al., 2021 ). All these observations give hope that Fe content and bioavailability are independent and feasible to integrate the two traits simultaneously.…”
Section: Nutrient Profiling Spatial and Temporal Distribution And Acc...mentioning
confidence: 99%